Drivers behavior for heavy truck operation in Kelantan: a perspective of truck drivers / Mohd Hafiz Afifi Azmi - Afifi Azmi, Mohd Hafiz (2022)
The frequency of road accidents, particularly those involving heavy trucks, has grown from time to time, based on the number of incidents on this day. Road accidents involving large heavy truck are caused by a variety of causes. The mindset of aggressive drivers is the most crucial element. Aggressive driving can take a variety of forms. Speeding, driving too close to the car in front of you, breaking traffic laws, inappropriate lane changes, and weaving are all examples of aggressive driving. However, most individuals who drive aggressively from time to time are completely unaware of it. As a result, when drivers, particularly those operating big cargo vehicles, drive aggressively, it is a major reason for worry. Road accidents involving heavy truck vehicles in the same location are a significant concern in Malaysia and other nations.